The academic and ideological inspirations of the oldest German writings concerning Lodz industry - Woźniak, Krzysztof Paweł (Acta Universitatis Lodziensis. Folia Germanica, 2017)
At the turn of 19th and 20th centuries the first academic writings on the Lodz textile industry were developed.Their authors were descendants of Lodz factory owners who studied at German universities (Frida Bielschowsky, Kurt Schweikert), as well as researchers not connected with Lodz (Róża Luksemburg, Alfred Scholz). The common feature of these research papers was their historical and economical view of the subject. The article characterizes the main thesis of the writings and shows the influence of Marxist theory as well as the ideas of the younger German school of economics. The sources of glorification in the presentation of the achievements and influence of German industrialists were also discussed.The article contains a thesis on the permanency of the Lodz industrial image which was created in the discussed academic writings.